Journal Information and Editorial Board - of Arts and Social Science, Idealogy Journal (Idealogy Journal; Vol 5 No 2 (2020): Idealogy Journal (September 2020), 2020)
This section presented about the Journal Information, Editorial Board, Panel of Reviewer, Copyright Notice, and Committee of Publication Ethic. This information for further reference by the author for the official needs on their own career path. Keyword: Journal Information; Editorial Board; Panel of Reviewer; Copyright Notice; Committee of Publication Ethic